Keabsahan Perkawinan Via Video Conference - Citra Riza, Anisa; Amin Qodri, M.; Muhammad Daud, Sulhi (Universitas Jambi, Fakultas Hukum, 2022)
This study aims to determine and analyze the validity of marriages and the application of marriage registration via video conference in Indonesia’s positive law which regulates marriage, namely Law Number 1 of 1974 concerning marriage. The issues raised are how the legality of marriage via video conference is in Indonesian positive law and how to apply marriage registration via video conference in Indonesian positive law. The method used is a normative juridical research type, using the Statute Approach, Conceptual Approach, and Case Approach. From the results of research on the validity of marriage via video conference in Law Number 1 of 1974 concerning Marriage, for the validity of a marriage, the State has left it entirely to every religion. So that if a marriage via video conference is declared valid according to religious law, then the marriage is declared valid under positive Indonesian law as long as it does not conflict with the provisions of the applicable legislation. Marriage registration via video conference for Muslims prefers marriages remotely by being represented using a power of attorney. Registration of marriages via video conference for non-Muslims must be legal according to the laws and regulations. That is, if the marriage is religiously legal (Article 2 paragraph (1) of the Marriage Law). so that those who marry by video conference are declared valid according to their religion, they are entitled to a marriage registration by the Civil Registry Office. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis keabsahan perkawinan dan penerapan pencatatan perkawinan via video conference dalam hukum positif Indonesia yang mengatur mengenai perkawinan yaitu Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan. Permasalahan yang diangkat yaitu bagaimana keabsahan perkawinan via video conference dalam hukum positif Indonesia dan bagaimana penerapan pencatatan perkawinan via video conference dalam hukum positif Indonesia. Metode yang digunakan adalah tipe penelitian yuridis normatif, dengan menggunakan Pendekatan Perundang-Undangan, Pendekatan Konseptual, dan Pendekatan Kasus. Dari hasil penelitian mengenai keabsahan perkawinan via video conference dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, untuk keabsahan suatu perkawinan Negara telah menyerahkan sepenuhnya kepada setiap agama. Sehingga apabila perkawinan via video conference dinyatakan sah menurut hukum agama maka perkawinan tersebut dinyatakan sah secara hukum positif Indonesia selama tidak bertentangan dengan ketentuan perundang-undangan yang berlaku. Pencatatan perkawinan via video conference bagi yang beragama Islam lebih menghendaki perkawinan secara jarak jauh dengan cara diwakilkan menggunakan surat kuasa. Pencatatan perkawinan via video conference bagi yang beragama non muslim pelaksanaannya harus sah menurut Peraturan Perundang-undangan. Maksudnya apabila perkawinan tersebut sah secara agama (Pasal 2 ayat (1) Undang-Undang Perkawinan). sehingga bagi mereka yang menikah secara video conference dinyatakan sah menurut agamanya berhak mendapatkan pencatatan perkawinan oleh Kantor Catatan Sipil.